PENGARUH PENERAPAN MODEL PEMBELAJARAN CORE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Rizki Sariningtias; Fadhilah Rahmawati; Zuida Ratih Hendrastuti (Jurnal Karya Pendidikan Matematika, 2022)
The purpose of this research is to describe the effectiveness of the application of the CORE learning model with mathematical problem-solving skills. This research is quasi-experimental research using a control group pre-test and post-test design. The subjects of this research are students of grades VII A and VII B at SMP Negeri 13 Magelang. Problem-solving ability data were collected using tests and analyzed using a t-test for the first hypothesis and an N-gain test for the second hypothesis. The results of the study show (1) that there is a significant difference in problem-solving abilities in the application of the CORE learning model compared to the direct learning model, and (2) there is a significant increase in problem-solving abilities in the application of the CORE learning mode than the direct learning mode. It can be concluded that the CORE model is effective in increasing mathematical problem-solving abilities.